Atypically Located Solitary Neurofibroma of the Ulnar Nerve as Inaugural Presentation of a New Genetic Variant of Neurofibromatosis Type 1: A Case Report - Carvalho, Diogo Rocha; Branco, Pedro Martins; Afonso, P. Diana; Gerardo, Gonçalo; Baptista, Carolina (Journal of hand surgery global online, 2022)
We report the case of a 34-year-old woman with hypothenar pain due to a solitary neurofibroma (NF) of the ulnar nerve, with an extrafascicular location, outside Guyon canal, with no clinical evidence of associated neurologic impairment, who was successfully treated with surgical resection. The identification of this isolated tumor led to the diagnosis of a new genetic variant of neurofibromatosis type 1 after genome sequencing. At the 1-year follow-up, the patient remains asymptomatic without recurrence or other peripheral nerve sheath tumors. A solitary NF of a deep-seated nerve is extremely rare, especially in the context of neurofibromatosis type 1. To our knowledge, there are no reports of a NF of the ulnar nerve with an extraneural location. In the presence of a solitary NF related to a deep-seated peripheral nerve, neurofibromatosis type 1 should always be excluded.